CHARACTERISTICS AND ASSESSMENT OF STUDENTS WITH LEARNING DISABILITY - Krishnarathi (International Journal of Research -GRANTHAALAYAH, 2016)
In every class there are probably some children with learning difficulties. Perhaps the child can-not learn to read fluently or may not be able to learn multiplication tables by heart. He or she may be slow at mental calculation or finds learning new motor skills problematic – there are many types of difficulties. During their career, every teacher meets several children for whom learning is laborious and even children who think that they cannot learn. Teaching these children is a challenge for the instructor. In fact, it is a challenge for the entire school. This article explain what are the characteristics of students with learning disability, how to identified the learning disability, assessment of learning disability and to guide them in helping students to overcome the challenges of learning difficulties.